Women's Perceptions and Gender Equality in the Context of Improving the Family Economy - Seffi Lolita; Ujang Jamaludin; Ronni Juwandi (CV. Rayyan Dwi Bharata, 2024)
As time goes by, demands for household needs increase and job opportunities and socio-cultural conditions become narrower. Not a few women choose to work abroad as Indonesian Migrant Workers. Gender equality in work is the government's responsibility to protect people's rights. For this reason, the government's role is needed in increasing gender awareness for female workers. The aim of this research is to describe women's perceptions regarding the existence of gender equality in the family economy and the related role of government for female workers. The method used is a qualitative descriptive approach. Data collection techniques through interviews, observation and documentation processes. The results of this research illustrate that there are differences in perception, namely 1) positive perception allows women to work 2) negative perception assumes that female migrant workers abandon their role as mothers resulting in a lack of harmony in the household. Then the regional government of Serang Regency, through DKBP3A, also created policies and assistance in implementing gender mainstreaming, including the Role of Gender Responsive Budgeting (PPRG), which was then socialized to each sub-district of Serang Regency.